Patient and Public Involvement in Stroke and Aphasia Research: a Thematic Analysis - Charalambous, Marina; Kountouri, Alexia; Phylactou, Phivos; Annoni, Jean-Marie; Kambanaros, Maria (My University, 2022)
Research Objectives To explore the views of people who live with chronic stroke and aphasia on their potential involvement as research partners. Design Qualitative study: semi-structured interviews. Participatory research model with a Patient and Public Involvement (PPI) partner: a person with chronic stroke-induced aphasia. Setting On line interviews (zoom). Participants Inclusion criteria: (1) to have experienced a stroke, (2) to be in the chronic stage of stroke (> 6 months post-stroke) (3) to speak, understand, read, and write English post-stroke (4) to be socially active as confirmed from the case history (5) to have at least one academic qualification, and (6) to have had previous research experience, whether as students or as researchers. An additional inclusion criterion for PWA was to show evidence, from case history interviews, of mild-moderate chronic aphasia. Participants Eight people with chronic stroke, four with concomitant aphasia and four without. Interventions N/A. Main Outcome Measures A thematic analysis following Braun and Clarke 6-step framework. Implementation of outcomes on the International Classification of disability F framework. Results Inductive thematic analysis generated four themes: (1) the kinds of Restrictions that make involvement in research difficult, (2) the preferred levels and ways of Involvement during the research process, (3) the Support required for active and collaborative involvement, and (4) the Impact of their involvement and how it benefits the study's outcomes. Conclusions People living with chronic stroke and aphasia are willing to be involved in PPI stroke and aphasia studies, if researchers provide the necessary robust support environment. The findings provide new evidence about how patient partnership models can support people with chronic communication deficits to contribute meaningfully to co-produced research.
Keywords: Chronic stroke; Aphasia